The aesthetic literacy in the youth and adult education - Gustavo Cunha de Araujo; José Carlos Miguel (Acta Scientiarum. Education, 2018)
This article is the result of a theoretical research and is part of a larger study under development in the doctorate program in Education of the State University Paulista Júlio de Mesquita Filho. It aims to understand the importance of aesthetic literacy for the development of reading and writing of young and adult students in rural education from readings and comic books productions. This study is based on Cultural-Historical theory and has as a method the Didactic-Formative Experiment. The data recording instruments used in the research are the field records of observations made in the classroom, the audio recording of interviews with the students, as well as visual records of the comic books produced by the students and classes recordings in videos. For data analysis, we will follow the perspective of Dialectical Historical Materialism. When considering reading and writing as social and cultural practices, literacy is fundamental in the educational process. In this sense, we understand that comic books are important instruments for the development of reading and writing of the young and adults of the rural education, allying text and image in the process of teaching and learning.